2017
DOI: 10.6001/biologija.v63i2.3528
|View full text |Cite
|
Sign up to set email alerts
|

Laelapidae mites (Acari: Mesostigmata) infesting small rodents in the Curonian Spit, Lithuania

Abstract: Laelapidae (Acari, Mesostigmata) mites are ecologically diverse and involve predators and parasites found in various habitats. In the present study, Laelapidae mites were collected from 236 small rodents of five species (the yellow-necked mouse Apodemus flavicollis, the harvest mouse Micromys minutus, the bank vole Myodes glareolus, the root vole Microtus oeconomus, and the field vole Microtus agrestis) in the Curonian Spit in 2013-2014. Five species of Laelapidae mites -Laelaps agilis, Hyperlaelaps microti, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The surprising result of this study is that we found only one parasitic species in the hamster burrows ( E. stabularis ). Parasitic mites were abundantly represented in nests of Mus spicilegus (Stanko et al ., 2007) and other small rodents (Büchner et al ., 2003; Kaminskienė et al ., 2017). Nevertheless, our result is somewhat consistent with the study of Bright and Morris (1996).…”
Section: Discussionmentioning
confidence: 99%
“…The surprising result of this study is that we found only one parasitic species in the hamster burrows ( E. stabularis ). Parasitic mites were abundantly represented in nests of Mus spicilegus (Stanko et al ., 2007) and other small rodents (Büchner et al ., 2003; Kaminskienė et al ., 2017). Nevertheless, our result is somewhat consistent with the study of Bright and Morris (1996).…”
Section: Discussionmentioning
confidence: 99%
“…Domains 1–3 from the 28S nuclear ribosomal RNA gene region and the COI gene of mitochondrial DNA were used for molecular characterization and phylogenetic reconstruction within the family Laelapidae [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…To amplify a 709 bp fragment of the COI gene, conventional PCR with primers LCO1490 (5’-GGT CAA CAA ATC ATA AAG ATA TTG G-3’) and HCO2198 (5’-TAA ACT TCA GGG TGA CCA AAA AAT CA-3’) was performed [ 33 ]. Each 25 µL reaction contained a mixture of 16.5 µL ddH 2 O, 5 µL 5× MyTaq reaction buffer (Thermo Fisher Scientific Baltics, Vilnius, Lithuania), 0.5 µL of each 10 mM primer, 0.5 µL MyTaq DNA polymerase (Thermo Fisher Scientific Baltics, Vilnius, Lithuania) (5 U/μL), and 2 µL DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The mites common and typical for birds of nests and small mammals are called nidicolous (Napierała and Błoszyk 2013 ). To date, most attention has been paid to mite fauna inhabiting nests of mammals (e.g., rodents, moles) and birds, such as storks, eagles, owls, pigeons, sea birds, and some passerine species (Kaźmierski 1998a ; Gwiazdowicz et al 1999 ; Kristofik et al 2002 , 2005 ; Błoszyk et al 2005 ; Pilskog et al 2014 ; Napierała et al 2016 ; Kaminskienė et al 2017 ; Kaźmierski et al 2018 , 2021 ; Celebias et al 2019 ). Those studies showed that the type of nest and the period when the nest is used play an important role in shaping mite assemblage structure.…”
Section: Introductionmentioning
confidence: 99%